Kajian terhadap Tingkat Kinerja Ekspor Indonesia dalam Rangka Meningkatkan Kesejahteraan Masyarakat Studi Kasus: Ekspor Udang Beku Indonesia - M Takdir Mulyadi (Bina Nusantara University, 2005)
The is aimed to know the performance level and the Indonesia’s Strategy of frozen shrimp export. The Research is done by using Revealed Comparative Advantage Analysis and SWOT Analysis. The result of this research showed that the level of Indonesia’s frozen shrimp export performance less than Thailand’s. The recommended strategy that can be done to increase the performance frozen shrimp export are: more focus in developing economic in fishery sector, investment, law deregulation in fishery sector